Causes and effects of the corrosion of a plumbing galvanised steel - Alejandre Sánchez, F. J.; Lucas Ruiz, R (Materiales de Construcción, 2002)
Hot dip galvanising life as a corrosion protective coatings on steel depends basically on three factors: coatings quality (thickness), correct installation of the galvanised article, and weathering effects. The aim of this research it is to study the decaying causes and effects of a plumbing installation made with hot dip galvanised steel tubes. The mentioned installation was of use during 30 years in the water supply system of the Parque Alcosa market (Sevilla, Spain). The research was divided in three parts: in the first one, shape analysis and XDR of internal decayed products was carried out: in the second one, physical properties were determined according to UNE 37- 505-89, corrosion morphology was conducted by metalographic microscopy, and it was evaluated also water quality: and finally, in the third one, diameter, section, and internal volume decrease was calculated in order to evaluate friction increase and pressure decrease in the installation. The results obtained show the correct plumbing installation according to quality requirements (UNE 37-509-89), so corrosion causes are mainly attributed to an aggressive environment for the hot dip galvanising.